Combination Effect of Laser, Antibiotics and Different Temperature on Locally Isolated Pseudomonas aeruginosa - Anwer, Ayad G.; Husien, Anssam S. (Iraqi Journal of Laser, 2007)
In humans, Pseudomonas aeruginosa is the second most frequent gram negative nosocomial pathogen in hospitals and has the highest case-fatality rate of all hospital-acquired bacteremia because of the hardy resistance of these bacteria to mechanical cleansing as well as to disinfectant, and many antibiotics. The susceptibility of bacteria against the antibiotics is modulated by several local factors such as temperature which modified drug efficacy, so this study was carried out to evaluate the effect of different temperature (20,42,45)Ċon the susceptibility of Pseudomonas aeruginosa to the minimum inhibitory concentrations (MIC) of the antimicrobial agents before and after irradiation. The samples collected from 150 persons suffering from burns-wounds infections, thirty-five isolates of pseudomonas aeruginosa bacteria were obtained depending on morphological and biochemical tests. Following exposure of Pseudomonas aeruginosa isolates to the diode laser with 805nm wavelength,3W output power and (5,10,15) minutes exposure times in combination with different temperature and different concentrations of ( cefotaxim, amikacin, chloramphenicol) antibiotics, highly observable change in the MIC value was achieved , the bacterial isolates became sensitive to chloramphenicol at the three exposure times and 100% killing of the cells was observed at 15 minutes exposure time at temperature 45Ċ in absence of the antibiotics. In conclusion, 3W diode laser in combination with temperature 45Ċ was the best condition that reduces the MIC value, and killing bacteria at 10 minutes exposure time.IntroductionSince the last century, the laser occupied a large degree of attention in the scientific and technological fields. Invention of laser causes a chain of important changes in the science development especially in physics, chemistry, biology and electronics, in addition to its industrial and medical applications. For this reason the laser enters in many fields and introduces solution to many problems.Many lasers have been used successfully for treating many cases of infection that caused by bacteria such as E.coli, Staphylococcus aureus and Pseudomonas aeruginosa. The resistance of Pseudomonas aeruginosa to many antibiotics form a big problem, especially in burns and wounds infections. Many studies have been introduced to investigate the effect of laser on microorganisms,a lotof their were related to the susceptibility of bacteria to antibiotics. This work is a trial in this regard.Pseudomonas aeruginosaOne of the most common microorganisms encounted in hospital infection. It was isolated from various sources like air, floor, sinks and even disinfectant (Iglewski, 1980).Pseudomonas aeruginosa is frequently present in